2021
DOI: 10.31603/pharmacy.v7i1.3021
|View full text |Cite
|
Sign up to set email alerts
|

Rational Drug Use (Rdu) Based on Patient Care Indicator in Primary Health Center in Semarang

Abstract: Rational Drug Use has several indicators, one of which is service indicators, where service indicators will play a role in increasing rational drug use so that it can support the success of treatment to achieve a better quality of life and patient welfare. The purpose of this study was to determine rational drug use in the city of Semarang based on service indicator parameters. This research is a descriptive-analytic with a cross-sectional design, data collection is done prospectively with a direct observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, malaria eradication has been prioritized to be targeted as one of the Millennium Development Goals (World Health Organization & WHO, 2020). Even though the incidence cases tend to decline in some areas (Febrinasari et al, 2021), there are five provinces with high malaria incidences are Papua, East Nusa Tenggara, West Papua, Central Sulawesi, and Maluku need to be prioritized and the resistance of chloroquine adds the complexity of problems. A prior study showed that resistance to antimalarials has been reported in both P falciparum and P. vivax and this resistance is not for chloroquine alone but also to currently used for antimalarials (Farooq & Mahajan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, malaria eradication has been prioritized to be targeted as one of the Millennium Development Goals (World Health Organization & WHO, 2020). Even though the incidence cases tend to decline in some areas (Febrinasari et al, 2021), there are five provinces with high malaria incidences are Papua, East Nusa Tenggara, West Papua, Central Sulawesi, and Maluku need to be prioritized and the resistance of chloroquine adds the complexity of problems. A prior study showed that resistance to antimalarials has been reported in both P falciparum and P. vivax and this resistance is not for chloroquine alone but also to currently used for antimalarials (Farooq & Mahajan, 2004).…”
Section: Introductionmentioning
confidence: 99%